Evaluation of periodontal indices in young adults submitted to chlorhexidine 0.12% mouthwash: a randomized clinical trial - Nathale Cruz BATISTA; Camila Possal de PAULA; Isis Andréa Venturini Pola POIATE; Edgard POIATE JUNIOR; Elizangela Cruvinel ZUZA; Gabriela Alessandra da Cruz Galhardo CAMARGO (Universidade Estadual Paulista, 2021)
Abstract Introduction Gingivitis is a gingival inflammation which can often be treated with oral hygiene such as brushing, flossing, and an antiseptic mouthwash. Objective The aim of this randomized clinical trial was to clinically evaluate the effectiveness of 0.12% chlorhexidine (CHX) solution as an anti-inflammatory agent and for reducing the presence of plaque and inflammation in young adults. Material and method Thirty patients with gingivitis aged 18 to 30 years with a probing depth ≤ 3 mm and a minimum of 20 teeth in the whole mouth were selected and evaluated at baseline and 30 days after treatment. Periodontal clinical parameters were verified: plaque index (PI), gingival index (GI), Simplified Oral Hygiene Index (OHI-S), Simplified Debris Index (DI-S), and Simplified Calculus Index (CI-S) Patients were then randomly allocated into two groups: CHX Group, received chlorhexidine 0.12% labeled as solution 1, and Placebo Group, received saline solution labeled as solution 2. Both groups were included in a hygiene program and received mouthwash. Result Statistically significant differences between CHX and Placebo groups were observed for the variables PI, GI, DI-S, CI-S, and OHI-S (p<0.05 - Paired T Test) after 30 days. The CHX group presented improved GI compared to Placebo at 30 days. Chlorhexidine 0.12% was efficient in the control of periodontium inflammation. Conclusion It can be concluded that chlorhexidine as a mouthwash is efficient in improving periodontal indices in young adults, but it is still controversial whether age can influence GI and OHI-S.